A novel voltage phase selector for inverter-interfaced system based on two-stage control strategy. (December 2021) - Chang, Peng; Song, Guobing; Hou, Junjie; Xu, Ruidong
Abstract: Due to the special fault features of the inverter-interfaced system, traditional phase selectors exist adaptability problems. In this paper, a novel voltage phase selector based on a two-stage control strategy is proposed, which is not influenced by the special features of the converter. First, the fault features of the converter during fault ride through (FRT) operation are analyzed. Second, using the high controlled-ability of the converter, the control strategy is divided into two stages by adding disturbances to the power references of the control system at the second control stage. On this basis, a novel superimposed sequence network is defined as the subtraction of the compound sequence networks under the first and the second control stage. Then, the phase-angle differences of sequence voltages in the novel superimposed sequence network are analyzed, which are not influenced by the fault features of the converter and can be used to establish phase selection criteria. The simulation results show that the proposed phase selection scheme is immune to the fault features of the converter system, fault resistance, fault location and the operation modes of the remote end system.